2021
DOI: 10.1016/j.ihj.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes in treatment of highly calcified coronary lesions with intravascular shockwave lithotripsy

Abstract: Real-world data regarding the efficacy and safety of coronary intravascular lithotripsy (IVL) are lacking. We conducted a study of 50 consecutive patients (64 lesions) who underwent IVL. 3 patients suffered in-hospital mortality unrelated to the IVL; there was no other occurrence of MACE up to 30 days. Angiographic success was nearly universal (98% of patients with residual stenosis <50%, 96% of patients with TIMI 3 flow) and complication was rare, including among patients undergoing IVL for in-stent restenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…with acute coronary syndromes and IVL treatment of in-stent restenosis have also reported favorable safety and effectiveness outcomes of coronary IVL with low rates of adverse clinical events at 1 year. 26,27 Thus, the relative 1-year benefits of IVL were sustained in both indirect comparisons with orbital atherectomy 28,29 and with historical cohorts of patients with moderate or severe target lesion calcification undergoing PCI with other lesion preparation techniques. 6,30,31 Nonetheless, adequately powered randomized trials are required to further evaluate the relative safety and effectiveness of different types of calcium-modifying therapies for calcified lesions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…with acute coronary syndromes and IVL treatment of in-stent restenosis have also reported favorable safety and effectiveness outcomes of coronary IVL with low rates of adverse clinical events at 1 year. 26,27 Thus, the relative 1-year benefits of IVL were sustained in both indirect comparisons with orbital atherectomy 28,29 and with historical cohorts of patients with moderate or severe target lesion calcification undergoing PCI with other lesion preparation techniques. 6,30,31 Nonetheless, adequately powered randomized trials are required to further evaluate the relative safety and effectiveness of different types of calcium-modifying therapies for calcified lesions.…”
Section: Discussionmentioning
confidence: 98%
“…[37][38][39] The safety and effectiveness of coronary IVL as an adjunct to stenting has been observed by others in smaller, initial "real-world" clinical experiences with limited 1-year follow-up. 26,27 Additionally,…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study of 50 patients who underwent IVL, 13 patients had ISR as the target lesion. Angiographic success occurred in 100% and none experienced death, MACE, or major bleeding at 30 days ( 152 ). Most recently, a prospective multicenter observational study of IVL in calcified coronary lesions included ISR with stent underexpansion in almost 30% ( n = 40) of the enrolled procedures.…”
Section: Management Of Restenosismentioning
confidence: 99%
“… 2 , 3 IVL has been shown to have excellent angiographic and short-term clinical results in patients with heavily calcified lesions who require percutaneous coronary intervention in both randomized and observational studies. 2 , 5 , 8 , 9 , 10 However, limited data exist regarding long-term outcomes. A recently published follow-up study of the Disrupt CAD III clinical trial cohort showed low rates of major adverse cardiac events (MACE), target vessel revascularization (TVR), and stent thrombosis at one year.…”
Section: Introductionmentioning
confidence: 99%
“…We previously published a study examining the immediate periprocedural and 30-day outcomes in a real-world IVL cohort; this study found nearly 100% angiographic success and low complications rates at 30 days. 10 In order to help better define long-term outcomes, we conducted a follow-up of the same high-risk cohort over a 1-year period following IVL.…”
Section: Introductionmentioning
confidence: 99%